Altererythrobacter muriae sp. nov., isolated from hypersaline Añana Salt Valley spring water, a continental thalassohaline-type solar saltern. Issue 3 (5th March 2021) - Azpiazu-Muniozguren, Maia; Martinez-Ballesteros, Ilargi; Gamboa, Javier; Seoane, Sergio; Alonso, Rodrigo; Laorden, Lorena; Garaizar, Javier; Bikandi, Joseba
Abstract : A novel salt-tolerant alpha-proteobacterium, designated SALINAS58 T, was isolated from Santa Engracia hypersaline spring water in the Añana Salt Valley, Álava, Spain. The isolate was Gram-negative, aerobic, non-motile, catalase-positive, oxidase-negative, rod-shaped and formed orange colonies on marine agar. Optimal growth was observed at pH 6.0–6.5, at 30 °C and in the presence of 1% (w/v) NaCl. The main cellular fatty acids (>20%) were summed feature 8 (C18 : 1 ω 7 c and/or C18 : 1 ω 6 c ) and summed feature 3 (C16 : 1 ω 7 c and/or C16 : 1 ω 6 c ). The major respiratory quinone was ubiquinone Q-10 and the major polar lipids detected were diphosphatidylglycerol, phosphatidylethanolamine, phosphatidilglycerol, four unidentified glycolipids and one unidentified phospholipid. Strain SALINAS58 T had the highest 16S rRNA gene sequence similarity to Altererythrobacter marensis MSW-14 T (96.6%), Altererythrobacter aquaemixtae JSSK-8 T (96.5%) and Pontixanthobacter luteolus SW-109 T (96.5%) followed by Altererythrobacter atlanticus 26DY36 T (96.4%). Results of the phylogenetic analysis, based on 16S rRNA gene sequences, and phylogenetic approaches based on whole genome nucleotide differences, showed that strain SALINAS58 T could be distinguished from recognized species of the genus Altererythrobacter . The genomic DNA G+C content was 61.4 mol%. Digital DNA–DNA hybridization, average nucleotide identity and average aminoacid identity values between the genome of strain SALINAS58 T and A. marensis MSW-14 T were 18.4, 73.1 and 68.1%, respectively. Based on data from this polyphasic characterization, strain SALINAS58 T (=CECT 30029 T =LMG 31726 T ) is considered to be classified as representing a novel species in the genus Altererythrobacter, for which the name Altererythrobacter muriae sp. nov. is proposed.